Street trees and intersection safety - Elizabeth Macdonald; Alethea Harper; Jeff Williams; Jason A. Hayter (University of California, Institute of Urban and Regional Development (IURD), 2006)
This study and report is about street trees and intersection safety in urban contexts. The study derives from a rather simple, straightforward observation: that on the best tree-lined streets the trees come close to the corners. They do not stop at some distance back from the intersecting street right-of-way. Indeed, in Paris, a city noted for its street trees, if the regular spacing of trees along the street runs short at an intersection, there is likely to be an extra tree placed at the corner. For at least 250 years, the finest of streets the world over have been associated with trees. Elm or oak shaded residential and commercial main streets remain as memories, but seldom as realities, of the best American urbanism. In the automobile age, a real concern with safety has resulted in street tree standards in the United States that dictate long setbacks from intersections, ostensibly geared to achieving unobstructed sight lines for drivers. But are street trees the safety problem they are purported to be? And are other physical, controllable qualities more important for preserving sight lines at intersections?
Keywords: 330